Analisis Penilaian Kinerja Karyawan Studi Pada Waiters Cafe Belly Buddy dengan Metode Behaviorally Anchor Rating Scale - Rizal Nazarudin A; Herman; Arie Ambarwati (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2023)
In the world of work, employee performance appraisal has an important role. This relates to decisions that will be taken by the company, related to the performance of its employees. As is the case with Cafe Belly Buddy, which is one of the culinary business ventures in Surabaya, is a company that of course conducts performance appraisals or evaluations for its employees. The method used by the current management of Cafe Belly Buddy is to carry out an evaluation process once every 3 (three) months, and the basis for the assessment has not used a structured method, so it is felt that it is still considered ineffective. This is because there are still many employees who consider formality, assessment is subjective, there are no clear and measurable standards, as well as feedback on employee performance achievements. As a result, employees feel uncomfortable and unmotivated at work. To overcome this, the authors compiled an employee performance assessment based on the method, namely using the Behaviorally Anchor Rating Scale (BARS) method. The Behaviorally Anchor Rating Scale (BARS) method can overcome the problem of evaluating employee performance which tends to be subjective in this case it can be used to meet the company's need for standards and feedback in employee performance appraisals. For this reason, the Behaviorally Anchor Rating Scale (BARS) method will be implemented for the waiters/waitress division which currently requires review and improvement in its performance process. By using this method, it is expected to be able to solve the problem of assessing the performance of waiters at Cafe Belly Buddy, so that finally employees can work comfortably and full of motivation and enthusiasm in carrying out their performance.